Development of Aqidah Akhlak Subjects Based on Scientific to Improve The Character of X Grade Students (SCHOOLAR: Social and Literature Study in Education, 2022)
This study aims to find out and get information about the application of the development   model of scientific-based moral  mapel development to improve the character of grade X students. This study uses a Research and Development (R&D) development model consisting of the following steps: exploring potentials and problems, data collection, product design, design validation, design revision, product trials, product revisions, usage trials, product revisions, mass production. Where in the purpose of this research is to develop and explain the use of moral teaching books. on the test validator experts produced that the product is said to be valid and  very  feasible because it gets  76% and as much as 24% is said to be feasible and at the initial product test stage produces an A score of  11  people (55%), and at the stage of the understandingtest with  20 students after memberi response to 15  statements showed the choice  of answers 75%  students  answered  correctly. And the students  who  answered one  as much as  25%.